2016
DOI: 10.1186/s12917-017-0976-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-generating compound GSNO suppresses porcine circovirus type 2 infection in vitro and in vivo

Abstract: BackgroundNitric oxide (NO), an important signaling molecule with biological functions, has antimicrobial activity against a variety of pathogens including viruses. To our knowledge, little information is available about the regulatory effect of NO on porcine circovirus type 2 (PCV2) infection. This study was conducted to investigate the antiviral activity of NO generated from S-nitrosoglutathione (GSNO), during PCV2 infection of PK-15 cells and BALB/c mice.ResultsGSNO released considerable NO in the culture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Supernatant from each sample was collected at different time points, then NO levels were quantitated by Griess reaction with a microplate reader at 540 nm and compared to a standard curve made from sodium nitrite. Data were presented as means ± SD from three independent experiments (**P < 0.01 vs the untreated control group, #P < 0.05 vs SNP-treated group) decreased PCV2 replication mediated by L-arginine, matrine and selenium was confirmed in vitro and/or in vivo [15,24,25]. Although the antiviral activity of NO has been proved by much research work, regulation of PCV2 replication induced by NO remains unknown to us.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Supernatant from each sample was collected at different time points, then NO levels were quantitated by Griess reaction with a microplate reader at 540 nm and compared to a standard curve made from sodium nitrite. Data were presented as means ± SD from three independent experiments (**P < 0.01 vs the untreated control group, #P < 0.05 vs SNP-treated group) decreased PCV2 replication mediated by L-arginine, matrine and selenium was confirmed in vitro and/or in vivo [15,24,25]. Although the antiviral activity of NO has been proved by much research work, regulation of PCV2 replication induced by NO remains unknown to us.…”
Section: Discussionmentioning
confidence: 97%
“…The antiviral activity of NO activity has been demonstrated against a variety of viruses including Marek's disease virus, astrovirus, dengue virus type 2, herpes simplex virus type 1 and Theiler's murine encephalomyelitis virus [10][11][12][13][14]. Our previous study show that NO-generating compound GSNO suppresses PCV2 infection in vitro and in vivo [15], and the other studies also confirmed that PCV2 replication could be suppressed by L-arginine in vivo [15,16]. As L-arginine is the natural precursor of NO [17], whether the inhibition of PCV2 induced by L-arginine is associated with NO, it remains unknown to us.…”
Section: Introductionmentioning
confidence: 93%
“…17‐Dimethylaminoethylamino‐17‐demethoxygeldanamycin (17‐DMAG), an inhibitor of Hsp90, is highly effective in suppressing PCV2 replication in BALB/c mice . Nitric oxide‐generating compound S ‐nitrosoglutathione (GSNO) treatment reduced the percentages of PCV2‐positive serum and tissue samples, as well as the viral DNA copies in the serum samples, indicating the reduction of PCV2 infection progression in mice . GSNO also improved the growth performance and immune organs (spleens and thymuses) of the PCV2‐infected mice .…”
Section: Evaluating Protective Chemicals and Antiviral Agents In Micementioning
confidence: 99%
“…Nitric oxide‐generating compound S ‐nitrosoglutathione (GSNO) treatment reduced the percentages of PCV2‐positive serum and tissue samples, as well as the viral DNA copies in the serum samples, indicating the reduction of PCV2 infection progression in mice . GSNO also improved the growth performance and immune organs (spleens and thymuses) of the PCV2‐infected mice . Lactobacillus reuteri significantly decreased the amount of PCV2 in the feces and in the ileum in mice, upregulated the gene expression of chemokines, interferon (IFN)‐γ, IgA and PIgR in the ileum, and significantly increased the percentage of CD19 + lymphocytes in the mesenteric lymph nodes and natural killer cells, indicating that probiotic L. reuteri has an antiviral effect on PCV2 in the intestine via stimulation of the local gut immune response .…”
Section: Evaluating Protective Chemicals and Antiviral Agents In Micementioning
confidence: 99%
See 1 more Smart Citation